2022
DOI: 10.1126/sciadv.add1267
|View full text |Cite
|
Sign up to set email alerts
|

An enzyme-mimic single Fe-N 3 atom catalyst for the oxidative synthesis of nitriles via C─C bond cleavage strategy

Abstract: The cleavage and functionalization of recalcitrant carbon─carbon bonds is highly challenging but represents a very powerful tool for value-added transformation of feedstock chemicals. Here, an enzyme-mimic iron single-atom catalyst (SAC) bearing iron (III) nitride (FeN 3 ) motifs was prepared and found to be robust for cleavage and cyanation of carbon–carbon bonds in secondary alcohols and ketones. High nitrile yields are obtained with a wide variety of functional groups. The prepared F… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
43
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 51 publications
(45 citation statements)
references
References 48 publications
2
43
0
Order By: Relevance
“…As depicted in Figure 6 f, the EPR signal displayed the characteristic fingerprint of spin adducts as a result of ·O 2 – , further confirming that the reactive oxygen species was ·O 2 – . 40 , 41 …”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…As depicted in Figure 6 f, the EPR signal displayed the characteristic fingerprint of spin adducts as a result of ·O 2 – , further confirming that the reactive oxygen species was ·O 2 – . 40 , 41 …”
Section: Resultsmentioning
confidence: 99%
“…Furthermore, the reactive oxygen species were explored during the oxidative transformation of N -ethylaniline into aniline over the ZnN 4 -SAC catalyst by radical inhibition experiments (Figure e and Table S9). , The conversion greatly decreased from 56% under the standard conditions to 10% in the presence of a radical scavenger of 2,6-di- tert -butyl-4-methylphenol (BHT), suggesting that the reaction should proceed via the radical reaction process. The presence of superoxide radical (·O 2 – ) scavengers (PBQ; 1,4-benzoquinone) greatly inhibited the reaction, while the addition of singlet oxygen (1O 2 ) scavengers (FA; furfuryl alcohol) and hydroxyl radical (·OH) scavengers (IPA; iso-propyl alcohol) showed no significant influence.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Recently, some research revealed that single‐atoms catalysts (SACs) [ 23 , 24 , 25 , 26 , 27 , 28 ] are the ideal candidate for the nanozymes because the atomically dispersed metal centers in SACs exhibit a high catalytic activity via maximized atomic utilization efficiency and active sites density. [ 29 , 30 ] Furthermore, the homogenous structure of metal atoms in SACs is an excellent platform to deeply understand the structure–activity relationships at the atomic level. The previous study [ 31 ] developed single iron atoms nanozymes (SANs) and proved their effectiveness for the O 2 activation in biosensing and biomedical.…”
Section: Introductionmentioning
confidence: 99%